Teaching NMR Using Online Textbooks - Joseph P. Hornak (Molecules, 1999)
Nuclear magnetic resonance (NMR) spectroscopy has almost become an essential analytical tool for the chemist. High-resolution one- and multi-dimensional NMR, timedomain NMR, and NMR microscopy are but a few of the NMR techniques at a chemist's disposal to determine chemical structure and dynamics. Consequently, even small chemistry departments are finding it necessary to provide students with NMR training and experience in at least some of these techniques. The hands-on experience is readily provided with access to state-of-the-art commercial spectrometers. Instruction in the principles of NMR is more difficult to achieve as most instructors try to teach NMR using single organic or analytical chemistry book chapters with static figures. This paper describes an online textbook on NMR spectroscopy called The Basics of NMR (http://www.cis.rit.edu/htbooks/nmr/) suitable for use in teaching the principles of NMR spectroscopy. The book utilizes hypertext and animations to present the principles of NMR spectroscopy. The book can be used as a textbook associated with a lecture or as a stand-alone teaching tool. Conference participants are encouraged to review the textbook and evaluate its suitability for us in teaching NMR spectroscopy to undergraduate chemistry majors.